2012
DOI: 10.1051/0004-6361/201118367
|View full text |Cite
|
Sign up to set email alerts
|

A tidal disruption-like X-ray flare from the quiescent galaxy SDSS J120136.02+300305.5

Abstract: Aims. The study of tidal disruption flares from galactic nuclei has historically been hampered by a lack of high quality spectral observations taken around the peak of the outburst. Here we introduce the first results from a program designed to identify tidal disruption events at their peak by making near-real-time comparisons of the flux seen in XMM-Newton slew sources with that seen in ROSAT. Methods. Flaring extragalactic sources, which do not appear to be AGN, are monitored with Swift and XMM-Newton to tra… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
131
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 147 publications
(135 citation statements)
references
References 81 publications
2
131
0
1
Order By: Relevance
“…Supernova explosions and expanding winds may emit hard X-ray flares (Immler & Lewin 2003;Chandra et al 2009;Saxton et al 2012). Supernova peak X-ray luminosities have been observed up to 10 40 erg/s with a decline usually following a t −(0.5−1) scaling.…”
Section: Phenomenologymentioning
confidence: 99%
“…Supernova explosions and expanding winds may emit hard X-ray flares (Immler & Lewin 2003;Chandra et al 2009;Saxton et al 2012). Supernova peak X-ray luminosities have been observed up to 10 40 erg/s with a decline usually following a t −(0.5−1) scaling.…”
Section: Phenomenologymentioning
confidence: 99%
“…In [12] we showed that the combined EPIC-pn, and MOS spectra for the three XMM-Newton observations are not well modelled by multi-coloured black-body emission. They were fit well by Bremsstrahlung radiation whose temperature declined from 390 ± 10 to 290 ± 20 to 180 +60 −30 eV as the X-ray luminosity dropped from 4.7×10 43 to 1.1 × 10 43 to 2.3 × 10 42 ergs/s.…”
Section: X-ray Spectrummentioning
confidence: 84%
“…In parallel, 30ks XMM-Newton pointed observations were triggered on 2010-06-22, 2010-11-23 and 2010-12-23. First results from these observations have been published in [12]. Further analyses, presented here, have been made with the XMM-Newton Science Analysis System (SAS v12; [3]).…”
Section: X-ray Follow-up Observationsmentioning
confidence: 99%
“…The first XMM-Newton observation was even fainter (by a factor of 2) than the other two XMM-Newton observations 2.4 years later. The X-ray spectral softening observed in XJ1231+1106 with the decrease in the X-ray flux has been observed in some TDE candidates (Lin et al 2011;Saxton et al 2012), but not in all cases. In the well monitored TDE candidate ASASSN-14li, steady blackbody temperatures in the X-ray spectra were observed despite the drop of the X-ray flux nearly by an order of magnitude (Miller et al 2015).…”
Section: The Tde Explanationmentioning
confidence: 94%